Prevention of Water Contamination as an Effort to Reduce the Incidence of Diarrhea in Pondok Pesantren Putri Wahid Hasyim Bangil - Farindra, Irmawan; Rusdi, Warda Elmaida; Dwijayanti, Ira; Shodiq, M.; Farakhin, Noer (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Wahid Hasyim Bangil Islamic Boarding School has thousands of students. With the large number of students who exist and live in one environment, it will certainly increase the incidence of diarrhea caused by water contamination and the incidence of diarrhea is very common in the cottage environment. Therefore, this activity aims to improve personal hygiene habits and Prevention of Water Contamination as an Effort to reduce the Incidence of Diarrhea in PP Putri Wahid Hasyim Bangil. Methods: This community service which was held in June 2023 was attended by 40 participants from PP Putri Wahid Hasyim Bangil. Activities carried out in the form of providing education, character building of students and administrators with health games and distribution of pretests and postests. This study was conducted descriptively observational to see the response of participants by looking at the enthusiasm and increase in knowledge of participants using Wilcoxon test analysis. Results: The results showed a p-value of 0.033. Because the value of 0.033 <0.05, it can be concluded that there is a difference between the knowledge of students before counseling (Pre-test) and after counseling (Post-test). Conclusion: There is an effect of providing counseling that has been carried out in community service activities at PP Putri Wahid Hasyim Bangil related to Prevention of Water Contamination as an Effort to reduce the Incidence of Diarrhea.